Design and implementation of high efficient switch mode power supply for a gel electrophoresis unit - Narayan, Giritharan (2010)
Nowadays, Switch Mode Power Supply (SMPS) is used widely in electronics systems. Many electrical appliances such as televisions and computer use SMPS to provide constant internal supply, SMPS also used to achieve higher voltage supply compared to powering batteiy voltage such as tape recorders, compact disc players, notebooks, mobile phones and cameras. Most critically, SMPS now is being used widely in biomedical research field since their efficiency and reliability to provide stable and constant configurable voltage range is required. Theoretically, SMPS provides 100% efficiency or lossless. However, in practical, SMPS has efficiency of 70% to 95% and this result to operation in low temperature and high reliability. Appreciating the contribution of SMPS in medical and science research environment, this thesis had focused on designing and implementing a switch mode power supply and for an electrochemical process named electrophoresis. Electrophoresis is defined as movement of particles through solvent under external electric field influence. There are several kinds of electrophoresis test and some of them require a DC power supply with some special characteristics. In this case, electric field was achieved by a Switched Mode Power Supply with characteristics such as wide range in output voltage (70-130v), output current reaching 300mA, and good voltage regulation.